Studi Deskriptif Mengenai Strength-Based Parenting pada Mahasiswa - Marissa Chitra Sulastra; Vida Handayani (Universitas Kristen Maranatha, 2021)
This research aims to get a description of strength-based parenting (SBP) on college students. The topic of parenting has been widely researched by experts. One of the parenting theories that is currently being developed from a positive psychological approach is strength-based parenting (SBP). The research about SBP, especially in Indonesia, is still limited. This research was conducted on 94 students of the Faculty of Psychology at